The Mediating Role of Trust in Strengthening the Influencing Relationship of a Number of Factors on Intentions to Invest in Cryptocurrency - Shwana Mohammed Amin Yousif Akoi (QALAAI ZANIST SCIENTIFIC JOURNAL, 2025)
The current research seeks to investigate the main factors influencing people's intentions to invest in cryptocurrencies. The problem statement of this study centers on examining the determinants of individuals' intentions to invest in cryptocurrency and assessing the impact of trust on these intentions. This research was conducted online using an academic questionnaire distributed to participants from various countries. Quantitative research methods were employed to analyze the primary factors influencing individuals' intentions to invest in cryptocurrency. The target sample size for this study was set at 385 citizens. The study's findings uncovered multiple factors influencing cryptocurrency investment intentions and underscored the pivotal role of trust in shaping individuals' investment decisions. To cultivate a more dependable and resilient cryptocurrency ecosystem, policymakers, regulators, and industry stakeholders should understand the mediating role of trust and address the underlying factors affecting investor trust. The study recommends prioritizing transparency and effective communication with investors, implementing strong security measures, and establishing clear regulatory frameworks to foster trust and confidence in the cryptocurrency industry.